'Environment' as a social concern: Democratising public arenas in Singapore? - KONG, Lily (Institutional Knowledge at Singapore Management University, 1994)
This paper explores the question of who defines the agenda of environmental concerns in Singapore. It argues that the state plays an inordinately large role in defining the agenda and implementing the solutions. Few other competing environmental agendas have been set in alternative public arenas. While this has worked generally well in Singapore, there are larger roles for environmental groups, businesses and industries, and other bodies to play. It is in the enlarged roles of these bodies that the hope for a greater democratization of public arenas in Singapore lies.